2004
DOI: 10.1074/jbc.m304528200
|View full text |Cite
|
Sign up to set email alerts
|

MARK4 Is a Novel Microtubule-associated Proteins/Microtubule Affinity-regulating Kinase That Binds to the Cellular Microtubule Network and to Centrosomes

Abstract: The MARK protein kinases were originally identified by their ability to phosphorylate a serine motif in the microtubule-binding domain of tau that is critical for microtubule binding. Here, we report the cloning and expression of a novel human paralog, MARK4, which shares 75% overall homology with MARK1-3 and is predominantly expressed in brain. Homology is most pronounced in the catalytic domain (90%), and MARK4 readily phosphorylates tau and the related microtubuleassociated protein 2 (MAP2) and MAP4. In con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
177
0
4

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(188 citation statements)
references
References 58 publications
7
177
0
4
Order By: Relevance
“…However, in this case the actin stress fibers are not rendered dynamic, and consequently focal adhesions are preserved and filopodia do not evolve ( Figure 7B, 3, 6, and 9). This experiment shows that active PAK5 NE has two independent effects on the cytoskel- The colocalization is concentrated on the pericentriolar region (merge, 9, arrows), reminiscent of MARK4 (Trinczek et al, 2004). The highest coincidence is observed with wild-type PAK5.…”
Section: Pak5 Inhibits Mark2 and Regulates The Stability Of Microtubumentioning
confidence: 69%
See 1 more Smart Citation
“…However, in this case the actin stress fibers are not rendered dynamic, and consequently focal adhesions are preserved and filopodia do not evolve ( Figure 7B, 3, 6, and 9). This experiment shows that active PAK5 NE has two independent effects on the cytoskel- The colocalization is concentrated on the pericentriolar region (merge, 9, arrows), reminiscent of MARK4 (Trinczek et al, 2004). The highest coincidence is observed with wild-type PAK5.…”
Section: Pak5 Inhibits Mark2 and Regulates The Stability Of Microtubumentioning
confidence: 69%
“…(7-9) Similar experiment with inactive YFP-PAK5 MM . The colocalization is concentrated on the pericentriolar region (merge, 9, arrows), reminiscent of MARK4 (Trinczek et al, 2004). The highest coincidence is observed with wild-type PAK5.…”
Section: Pak5 Inhibits Mark2 and Regulates The Stability Of Microtubumentioning
confidence: 76%
“…We identified 5 transcripts down‐regulated upon miR‐515‐5p overexpression: NRAS, FZD4, CDC42BPA, PIK3C2B and MARK4 (Fig 2A), and these were validated by qPCR (Fig 2B and C). These transcripts have been described as being involved in cell migration and are predicted by TargetScan to be directly targeted by miR‐515‐5p 6, 12, 13, 14, 15. Furthermore, we validated this using luciferase report assays that demonstrated that miR‐515‐5p interacts directly with the 3′ UTR of NRAS, PIK3C2B and MARK4 (Fig 2E and F) and showed the same targets to be down‐regulated by miR‐515‐5p in NSCLC cells (Fig 2D).…”
Section: Discussionmentioning
confidence: 99%
“…For the detection of NGC, cells were incubated with either monoclonal anti-NGC antibody C5 (30) or polyclonal rabbit anti-NGC antiserum (30). For the staining of tubulin, cells were treated as described (31) and incubated with monoclonal anti-␤-tubulin antibody (clone2-28-33, Sigma). Cells were also stained by monoclonal anti-Myc tag antibody (clone 9E10, Upstate Biotechnology, Lake Placid, NY).…”
Section: Methodsmentioning
confidence: 99%